Предмет: Математика,
автор: Rauna2008
(2(x+y)-x+6=0, 3x-(x-y)=0
Ответы
Автор ответа:
9
Ответ:
2Х + 2Y - X = - 6
X = - 6 - 2Y
----------------
3X - X + Y = 0
2X + Y = 0
2X = - Y
- 12 - 4Y = - Y
- Y + 4Y = - 12
3Y = - 12
Y = - 4
---------
X = - 6 - 2 * ( - 4) = - 6 + 8 = 2
Пошаговое объяснение:
sartur59515:
X=-6-2y
Похожие вопросы
Предмет: Русский язык,
автор: лабрик
Предмет: Русский язык,
автор: milasalkova
Предмет: Русский язык,
автор: verastativa
Предмет: Математика,
автор: dimaShamigulov
Предмет: Математика,
автор: kekkek11